Behaviour characteristics estimation tool of genetic distance between sheep breeds - Eko Handiwirawan; Ronny Rachman Noor; Cece Sumantri; Subandriyo . . (Indonesian Center for Animal Research and Development (ICARD), 2014)
Information on the estimation of genetic distances and differentiation among sheep breeds are needed in crossing and conservation programs. This research aims to study of utilizing behaviour characteristic variables to differentiate and estimate genetic distance between the sheep breeds. The study was conducted at Cilebut and Bogor Animal House of Indonesian Research Institute for Animal Production. Five sheep breeds used were Barbados Black Belly Cross (BC), Garut Composite (KG), Garut Local (LG), Sumatera Composite (KS) and St. Croix Cross (SC), with total sample of 50 heads. A total of 10 variables of behavior traits were observed in this study. Analysis of variances and significance tests were applied to compare between sheep breeds and performed for all of behavior traits using PROC GLM of SAS Program ver. 9.0. PROC CANDISC was used for canonical discriminant analyses, the hierarchical clustering was performed using the PROC CLUSTER by Average Linkage method (Unweighted Pair-Group Method Using Arithmetic Averages, UPGMA), and the dendogram for the five sheep breeds was described using PROC TREE. The differentiator variables for the behavior traits were standing and feeding duration. The canonical plotting based on behavioral characteristics could differentiate BC, KS and LG (with KG and SC) sheeps. Estimation of genetic distance based on the behavior traits is less accurate for grouping of sheep breeds.